To divide \( 36\sqrt{39} \) by \( 9\sqrt{13} \), follow these steps:
\[ \frac{36\sqrt{39}}{9\sqrt{13}} \]
First, divide the coefficients:
\[ \frac{36}{9} = 4 \]
Now, write the expression with the square roots:
\[ 4 \cdot \frac{\sqrt{39}}{\sqrt{13}} \]
Using the property of square roots, we can simplify the fraction:
\[ \frac{\sqrt{39}}{\sqrt{13}} = \sqrt{\frac{39}{13}} \]
Now simplify \( \frac{39}{13} \):
\[ \frac{39}{13} = 3 \]
Thus,
\[ \sqrt{\frac{39}{13}} = \sqrt{3} \]
Now, we can combine our results:
\[ 4 \cdot \sqrt{3} \]
The final result is:
\[ 4\sqrt{3} \]